Analysis of determinant factors of literacy in strengthening students' religious character - Zulkifli Zulkifli; Ery Wati; Intan Mauliza; Muchsin Muchsin (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study analyzes the determinant factors of digital literacy, cultural literacy, and religious literacy in strengthening students' religious character, with a specific focus on the mediating role of self-efficacy. The research employed a quantitative method, conducting a survey of 57 junior high school students. The collected data were analyzed using Structural Equation Modeling (SEM). The results demonstrate that all three forms of literacy have a significant direct influence on religious character, with religious literacy being the strongest predictor. Furthermore, self-efficacy was proven to be a significant partial mediator. Specifically, religious, cultural, and digital literacy positively influence self-efficacy, which in turn strengthens religious character. These findings conclude that strengthening religious character in the modern era requires an integrative approach. This approach must not only build cognitive competencies through multiple literacies but also simultaneously develop students' psychological self-belief (self-efficacy) to apply these religious values within complex digital and cultural contexts.